Migration, Flucht und der liberale Staat - Miller, D (De Gruyter, 2017)
This paper asks how a modern liberal state that wishes to remain true to its own values should respond to mass inward migration. Three of those values – freedom, equality of opportunity, and human rights – appear to support fully open borders. But a democratic welfare state needs citizens who trust one another, and this in turn raises questions of cultural identity. The cultural integration of immigrant groups requires limits to the numbers being admitted, and the selection of those who will become citizens in future. A closer inspection of the three open borders arguments reveals that none of them is decisive. In particular, immigration is not a human right. Nevertheless refugees, whose human rights are imperilled, may have strong claims to be admitted by liberal states. Ideally these claims should be met by setting up an international burden-sharing scheme. Where refugee numbers are so high as to impose severe costs on the receiving state, the decision to admit needs to be democratically authorised.